Pengaruh Gaya Kepemimpinan Dan Lingkungan Kerja Terhadap Motivasi Kerja Pegawai Pada Dinas Perhubungan Provinsi Sumatera Barat - Sabrina Ananda Zuliani; Ezizwita, Ezizwita (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to determine the effect of leadership style and work environment on employee work motivation at the west Sumatra provincial transpotation agency. This study uses a quantitative approach with a saturated/census sampling method of 52 employees. Data were collected through a hierarchical questionnaire (Likert scale) and analyzed using descriptive analysis techniques, classical assumption test, multiple linear regression, hypothesis testing and determination coefficient analysis (R2). The results of the study based on partial hypothesis testing (T test) show that leadership style variable has a positive and significant effect on work motivation and factors related to the work environment have a positive and significant impact on work motivation. Based on sumultanneous hypothesis testing (F test) shows that the leadership style and work environment variables have a significant positive effect on work motivation